VD_FINDINFO ML / 2013 / 87 vom 11. April 2013 - VD Tribunal cantonal (2013)
CALCUL DU DÉLAI, DÉLAI, DÉLAI DE GARDE, OBSERVATION DU DÉLAI, NOTIFICATION DE LA DÉCISION | 138 al. 3 let. a CPC (CH), 142 al. 1 CPC (CH), 239 al. 1 CPC (CH)